DESIGNING SPACECATION (SPEAKING APPLICATION) FOR NON ENGLISH DEPARTMENT STUDENTS - Ulfa Wulan Agustina (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2022)
ABSTRACT This study aims to design a learning media for non English department students named SPACECATION (Speaking Application), thislearning media application can help students in learning speaking skills. The method used in this research is Research and Development .This development used ADDIE models which have 5 steps : 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. This media was validated by media expert and material expert before trying out to the students. The instrument of this research, were questionnaires and interviews to media expert, material expert, and students. The result of this research are : 1) the result of media expert was 94,1 scores in “Very good” category, 2) the result of material expert was 84 scoresin “Very good” category, 3) the result of a questionnaire for students responses was 89 in “Very good” classification. Based on the result, the researcher conclude that students are interested in learning English speaking skill and SPACECATION(Speaking Application) can helps students in their learning process in speaking skill. Furthermore, this research can be used as a reference to another researcher with different skills or subjects of the research. KEYWORDS: Speaking skill, Learning media, SPACECATION ABSTRAK Penelitian ini bertujuan untuk mendesin media pembelajaran untuk selain mahasiswa pendidikan bahasa inggris dengan nama SPACECATION (Speaking Application), media aplikasi ini dapat membantu mahasiswa untuk pembelajaran speaking. Metode yang digunakan dalam penelitian ini adalah Research and Development. Pengembangan ini menggunakan model ADDIE yang memiliki 5 step : 1) Analysis 2) Design 3) Development 4) Implementation 5) Evaluation. Media ini sudah divalidasi dengan validasi media dan validasi materi sebelum uji coba kepada mahasiswa. Instrumen dari penelitian ini adalah kuestioner dan interview untu kahli media, ahli materi, dan mahasiswa. Hasil dari penelitian ini adalah : 1) hasil dari ahli media adalah 94,1 dengan kategori “sangat bagus”, 2) hasil dari ahli materi adalah 84 dengan kategori “sangat bagus”, 3) hasil dari kuestioer respon mahasiswa adalah 89 dengan klasifikasi “sangat bagus”. Berdasarkan hasil penelitian, peneliti menyimpulkan bahwa mahasiswa tertarik dengan pembelajaran bahasa inggris dan SPACECATION (Speaking Application) dapat membantu mahasiswa dalam proses pembelajaran speaking skill. Selanjutnya, penelitian ini dapat digunakan sebagai referensi dengan kemampuan yang berbeda data subjek yang berbeda dari penelitian. Kata kunci : speaking skill, learning media, SPACECATION.